Bulk grain boundary decoration and functionally-graded alloy developed by one-step friction stir process: Experiment and atom probe tomography analysis - Mina Dehghan; Priti Wanjara; Javad Gholipour; Ahmed A. Tiamiyu (Materials & Design)
Conventionally-manufactured lightweight metal castings typically exhibit low-strength that can be improved by grain-refinement. Meanwhile, refined-grain materials often undergo grain-growth at elevated or even room temperature, degrading mechanical/functional properties. Current thermodynamic grain-stabilizing approach is either limited to a thin-film-scale or relies on a two-step mechanical-alloying and heat-treatment process. To circumvent these limitations, this study proposes using friction stir-processing (FSP) to develop bulk grain-boundary (GB)-decorated nanograined materials. We hypothesized that the high strain/strain-rate during FSP produces grain-refinement, while the temperature-rise simultaneously drives solute to the solvent-GBs. Developed GB-segregation map for aluminum-Al solvent identifies magnesium-Mg as a suitable solute-element that will segregate at Al-GBs. Two different FSP traverse speeds—low-432 mm/min and high-1040 mm/min—at a fixed rotational speed were examined on an Al-Mg-Al sandwich configuration that produces microscale-functionally-graded materials (FGMs). Lower traverse-speed promotes higher heat-input, material flow, microcracks formation, mixed zones, and mechanical hooks near the Al-Mg interfaces, while higher traverse-speed results in lower heat-input, crack-free Al-Mg interfaces, mechanical mixing, and isolated-mixed zones. Using atom-probe-tomography (APT), a nanoscale functionally-graded intermediate region constituting solid-solution, GB-segregation, β-phase, and γ-phase is observed towards the Al-Mg-interface. APT also confirms how the β-phase might have evolved via a spinodal decomposition phenomenon in support of evidence of a miscibility gap in the Al-Mg alloy that was reported about four decades ago. This work offers innovative materials processing that opens new possibilities for structural use of bulk stable-nanocrystalline materials and FGMs.